Daya Terima, Nilai Gizi, dan Kandungan Serat Burgo dengan Penambahan Jamur Tiram Putih (Pleurotus Ostreatus) Dan Rumput Laut (Eucheuma Cottonii) untuk Menu Sarapan Lansia - Ramadhani, Vidhea Anisa; Hartati, Yuli; Sriwiyanti, Sriwiyanti; Sadiq, Ahmad (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Background: Elderly people have a tendency to consume foods that contain little fiber, resulting in less fiber intake. The innovation of burgo with the addition of white oyster mushrooms and seaweed is an alternative high-fiber food. Objective: To find out the acceptance, best formulation, differences in each acceptances, nutritional value, and fiber content of burgo with the addition of white oyster mushrooms and seaweed as a breakfast menu for the elderly. Methods: This study was an experimental study using a non-factorial Completely Randomzed Design (CRD) with 3 formulations off adding white oyster mushrooms and seaweed F1 (75g:150g), F2 (100g:125g), F3 (125g:100g). The subjects of this study was organoleptic with 35 of panelist using the Kruskal Wallis test and continued by Mann-Whitney test. Result: Organoleptic tests (color, aroma, texture, taste, aftertaste, and overall) showed the most preferred that acceptance of burgo with the addition of white oyster mushrooms and seaweed F2 with energy 85,83 kcal, protein 4,40 gram, fat 1,99 gram, carbohydrates 10,34 gram, and fiber 1,56 gram. Kruskal Wallis test showed the significant results on aroma, texture, and aftertaste. Conclusion: Burgo with the addition of white oyster mushrooms and seaweed can be used as an alternative breakfast menu for the elderly with source of high fiber